Avaliação do carvão ativado da torta prensada de Raphanus sativus como adsorvente para a remoção de corantes básicos presentes em soluções aquosas diluídas - Daniela Aparecida Lazaro (2009)
The performance of the cold-pressed cake from Raphanus sativus (L. Var.) oilseeds activated carbon, a solid residue from biodiesel production, was evaluated as an adsorbent for basic dyes. The main objective is to use the adsorbent in the treatment of effluents generated by textile industries. Methylene blue (MB) dissolved in dilute aqueous solutions was chosen as the adsorbate. The study comprised two main steps. In the first step, activated carbon from Raphanus sativus (L. Var.) cold-pressed cake was produced and adsorption tests focusing on the evaluation of equilibrium, kinetics and the effects of main operational parameters were conducted. Batch adsorption tests were performed at room temperature (25oC) and the effects of particle size, contact time, adsorbent dosage and pH were investigated. Adsorption kinetics was determined by fitting first and second-order kinetic models to the experimental data, with the second-order model providing the best description for MB adsorption onto the prepared adsorbent. The adsorption process can be described by a two-stage kinetic behavior, with a rapid initial adsorption during the first 6 hours, followed by a much slower rate afterwards. Equilibrium was attained after 12 hours for an initial dye concentration of 100 mg L-1 .The experimental adsorption data after 72 hours were fitted to Langmuir and Freundlich adsorption models, with the former model providing the best fit. Langmuir based maximum MB uptake capacity was 19.8 mg.g-1, higher than other adsorbents employing similar types of residues such as sunflower oil cake, coffee seeds press cake and date pits. The second part of the study comprised the characterization of the activated carbon. It was focused on the study of the morphology of the adsorbent, including textural properties such as surface area, total volume and average pore diameter as well as the structural variation of Raphanus sativus (L. Var.) (L. Var.) activated carbon before and after MB adsorption. Classical characterization methodologies such as surface area calculation through the Brunauer-Emmet-Teller method (BET), pore parameters calculation through Barret-Joyner-Halenda method (BJH) and morphological adsorbent characterization through Scanning Electron Microscopy (SEM) and X-ray Energy Dispersive Spectrometry as well as Raman spectroscopy that was found to be a potential method to physical characterization of the porous structure of activated carbons and as a tool to study the adsorption mechanism of an activated carbon, through the determination of adsorption bonding between activated carbon and adsorbate. A microporous structure was verified qualitatively (SEM and Raman analysis) indicating that MB adsorption occurs predominantly at the surface of the adsorbent (surface area = 236.3 m2.g-1, pore volume = 0.06 cm3.g-1; pore size = 1.4 nm). Adsorption probably occurs by MB bonding of monomer species through central nitrogen atom